How to make and justify a decision: the analytic hierarchy process. Part 1. Examples and Applications - Saaty, T.L. (Системні дослідження та інформаційні технології, 2002)
We describe and discuss a logical approach, the Analytic Hierarchy Process (AHP), that can be used to make decisions. It involves breaking the problem down into finer and finer parts so that one is called upon to give a judgment comparing only a pair of issues in each judgment.